Nathan's Opposition to David’s Intention to Build a Temple in the Light of Selected Ancient Near Eastern Texts - Ulshoefer, H. K.
Diss.; pattern of temple-building after defeating powers of chaos found in myth and history; Cf. Diss. Abstr. 73 (1976-77) 7811-A (Order No. 77-11, 426).